2022
DOI: 10.3390/cancers14133091
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin Distinguishes Intrahepatic Cholangiocarcinoma from Liver Metastases of Ductal Adenocarcinoma of the Pancreas

Abstract: Carcinomas of the pancreatobiliary system confer an especially unfavorable prognosis. The differential diagnosis of intrahepatic cholangiocarcinoma (iCCA) and its subtypes versus liver metastasis of ductal adenocarcinoma of the pancreas (PDAC) is clinically important to allow the best possible therapy. We could previously show that E-cadherin and N-cadherin, transmembrane glycoproteins of adherens junctions, are characteristic features of hepatocytes and cholangiocytes. We therefore analyzed E-cadherin and N-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Having demonstrated the formation of E:N-cadherin heterodimers in the liver, a feature that is highly preserved during hepatocarcinogenesis, the presence of both cadherins may be used for the differential diagnoses of carcinomas of unknown primary. In line with this, we have previously shown the presence of E- and N-cadherin in cholangiocytes of the biliary tree and derived tumors, suggesting N-cadherin as a marker to distinguish between intrahepatic cholangiocarcinoma and liver metastases of ductal adenocarcinoma of the pancreas [ 89 ]. In conclusion, E- and N-cadherin are suitable markers to identify hepatocytes, cholangiocytes, and derived tumors.…”
Section: Discussionsupporting
confidence: 62%
“…Having demonstrated the formation of E:N-cadherin heterodimers in the liver, a feature that is highly preserved during hepatocarcinogenesis, the presence of both cadherins may be used for the differential diagnoses of carcinomas of unknown primary. In line with this, we have previously shown the presence of E- and N-cadherin in cholangiocytes of the biliary tree and derived tumors, suggesting N-cadherin as a marker to distinguish between intrahepatic cholangiocarcinoma and liver metastases of ductal adenocarcinoma of the pancreas [ 89 ]. In conclusion, E- and N-cadherin are suitable markers to identify hepatocytes, cholangiocytes, and derived tumors.…”
Section: Discussionsupporting
confidence: 62%
“…We previously demonstrated that the co‐expression of E‐ and N‐cadherin is a characteristic of hepatocytes, cholangiocytes, and their derived tumors 17,18 . To test the potential of E‐ and N‐cadherin as markers in the differential diagnosis of PLC vs extrahepatic carcinomas, their expression was assessed in a total of 13,295 individual TMA cores comprised of 3359 different tumors (Tables 1 and 2), and compared to previously published analyses of 882 cases of PLC, including HCC and iCCA 17,18 . In a first step, we investigated E‐cadherin (Figure S1) and N‐cadherin (Figure 1) expression via immunohistochemistry (Tables 1, S2, and S3).…”
Section: Resultsmentioning
confidence: 99%
“…Primary tumors, lymph node metastases, and distant metastases were each separately evaluated. This method, which we have applied in previous studies 17,18 has proven to reflect the most precise gradation of staining intensity for E‐ and N‐cadherin in our experience. Sensitivity and specificity were calculated using Microsoft Excel 2016 (Microsoft Corporation, Redmond, WA).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations